Money Management, Financial Security, dan Financial Behavior: Peran Mediasi Financial Stress - Candy Candy; Johny Budiman; Kristine Gladis Feby; Deandra Emilya Putri; Cheisya Nabilah; Fathir Suria Marika Putri; Tasha Rahmatika (Universitas Multi Data Palembang, 2026)
This study aims to analyze the effect of current money management stress and expected future financial security on financial behavior, with financial stress as a mediating variable among individuals of productive age in Indonesia. This study adopts a quantitative approach using a survey method through the distribution of online questionnaires to respondents aged 17–64 years. The sampling technique applied is non-probability sampling using the convenience sampling method. Data were analyzed using structural equation modeling based on partial least squares with the assistance of SmartPLS software. The findings indicate that current money management stress has a significant effect on financial stress and financial behavior, while expected future financial security significantly affects financial behavior. However, financial stress is not found to mediate the relationship between independent variables and financial behavior.